Outcomes of very high-power short-duration ablation using 90w for pulmonary vein isolation in patients with atrial fibrillation: a real world observation study. (3rd October 2022) - Mavilakandy, A; Antoun, I; Kotb, A; Koev, I M; Barker, J; Vali, Z; Sidhu, B; Pooranachandran, V; Li, X; Ng, G A
Abstract: Introduction: Pulmonary vein isolation (PVI) ablation is the established gold standard therapy for patients with symptomatic drug refractory atrial fibrillation (AF). Advancements in radiofrequency (RF) ablation, have led to the development of the novel contact force-sensing temperature-controlled very high-power short-duration (vHPSD) RF ablation. This setting delivers 90W for up to 4 seconds with a constant irrigation flow rate of 8ml/min. The aim of this study was to compare procedural outcomes and safety with conventional radiofrequency ablation. Methods: An observational study was conducted with patients who underwent first time PVI ablation from 2019 to 2021. The cohort was divided in to: 1) vHPSD ablation – QMODE+ via QDOT MICRO catheter, 2) QMODE via QDOT MICRO catheter and 3) Conventional power-controlled RF (PCRF) ablation via THERMOCOOOL SMARRTOUCH SF (STSF) catheter. The QMODE+ vHPSD ablation group was prospectively recruited while the QMODE and PCRF group were retrospectively collected. Primary outcomes were procedural success, PVI duration, ablation duration and incidence of perioperative adverse events. Secondary outcomes were intraprocedural morphine and midazolam requirement. Results: A total of 155 patients were included in the study with 80, 30 and 45 patients in the QMODE+ (vHPSD), QMODE and PCRF, respectively. PVI was successfully attained in all patients. QMODE+ (vHPSD) demonstrated significantly reduced time required for PVI and total energy application in comparison to the QMODE and PCRF groups (68.3±3.30 vs. 92.9±4.86 vs. 93.6±4.34 min, P<0.0001; 9.7±0.452 vs. 33.9±0.452 vs. 36.0±1.56 min, P<0.0001, respectively) (Figure 1). Intravenous morphine and midazolam requirement was lower in the QMODE+ (vHPSD) group compared to the QMODE and PCRF groups (10.3±0.45 vs. 16.1±0.935 vs. 15.3±0.686 mg, P<0.0001; 4.05±0.402 vs. 8.63±1.07 vs. 8.58±0.821 mg, P<0.0001) (Figure 2). QMODE+ (vHPSD) observed a non-significant reduction in fluoroscopy time compared to QMODE and PCRF. One cardiac tamponade were observed in both the QMODE+ (vHPSD) and QMODE group while the PCRF group exhibited an embolic stoke and two pericardial effusions that did not require drainage. Conclusion: In this study, QMODE+ (vHPSD) demonstrated a comparable safety profile to the other treatment arms. Procedural duration and energy application time was substantially reduced while a non-significant reduction was observed for fluoroscopy time for QMODE+. Furthermore, sedation requirement was reduced and thus potentially conveyed greater patient tolerability of the procedure when conducted with QMODE+. Notwithstanding the limitations of observational study design, these preliminary findings are promising with respect to periprocedural outcomes and safety of QMODE+. Longer term outcomes with respect to maintenance of sinus rhythm and symptomatic burden will be essential to assessing the overall efficacy of this novel technology. Funding Acknowledgement: Type of funding sources: None.